2010
DOI: 10.1002/srin.200900154
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Behaviour of some Steelmaking Slags

Abstract: The present study was aimed at highlighting the final properties of two different steelmaking slags which undergo different cooling rates. The experiments were conducted in laboratory scale using an induction furnace. One of the slags originates from an electric arc furnace (EAF) (high‐alloyed) and the second slag from a basic oxygen furnace (BOF). The treatment of the slag included re‐melting along with different cooling rates. The material collected from the tests was characterized through X‐ray diffraction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 9 publications
1
54
0
Order By: Relevance
“…Those prior characterization tests resulted in the following major findings: (1) The EAF slag used in these experiments were principally composed of iron (Fe) and calcium (Ca), as previously noticed in other studies on EAF slag [34][35][36], and were present as Wüstite (FeO), Larnite (β-Ca 2 In this study, characterization was extended to spent slag specimens from the treatment of other synthetic stormwater systems in Table 2. BET (Brunauer-Emmett-Teller) surface area determination was carried out to ascertain if physisorption occurred in all cases, especially in the case of the Cudominant system, P + Cu, where significantly lower P removal had been observed.…”
Section: Characterization Of Slagmentioning
confidence: 68%
“…Those prior characterization tests resulted in the following major findings: (1) The EAF slag used in these experiments were principally composed of iron (Fe) and calcium (Ca), as previously noticed in other studies on EAF slag [34][35][36], and were present as Wüstite (FeO), Larnite (β-Ca 2 In this study, characterization was extended to spent slag specimens from the treatment of other synthetic stormwater systems in Table 2. BET (Brunauer-Emmett-Teller) surface area determination was carried out to ascertain if physisorption occurred in all cases, especially in the case of the Cudominant system, P + Cu, where significantly lower P removal had been observed.…”
Section: Characterization Of Slagmentioning
confidence: 68%
“…It may be difficult to avoid the formation of the minerals, such as melilite and merwinite, in the EAF slag [9][10], but the addition of FeO reduces the content of Cr in these minerals. Therefore, FeO could be considered as an effective additive for a positive Cr distribution in the slag, by which Cr is bonded largely in stable spinel minerals and the dissolution of Cr-free silicates does not cause Cr leaching.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of García-Ramos et al [8] also showed that the Cr leachability has been suppressed by the presence of MgO or Al2O3 in the slag system of CaO-SiO2-Cr2O3, with the efficiency of MgO for the leaching suppression higher than that of Al2O3, due to the stable binding for Cr in MgCr2O4. In addition, the mineralogical and microstructural analyses performed by Tossavainen et al [9] and Engström et al [10] have shown that merwinite (Ca3MgSi2O8), akermanite (Ca2MgSi2O7), gehlenite (Ca2Al2SiO7), and spinels were major phases in the EAF slag. Jelkina et al [11] found that the amount and purity of mineralogical phases present in the synthetic slags of the CaO-MgO-SiO2-Cr2O3-Al2O3 system were highly dependent on the slag composition and heat treatment history.…”
Section: Introductionmentioning
confidence: 98%
“…However, the difference at cooling rates under 80°C/min was not significant as there was still time for the crystals to nucleate and grow. Generally speaking, the crystal size under slow cooling conditions is larger than that under rapid cooling [32][33][34]. As the cooling rate increased, insufficient time for crystal growth and the increasing viscosity lowered the diffusion of ions.…”
Section: Continuous Cooling Conditions and Cct Diagrammentioning
confidence: 98%